Advanced introduction to urban transport planning - Krizek, Kevin J. (Elgar advanced introductions, 2021)
Insightful and original in its approach, this Advanced Introduction to Urban Transport Planning provides a fresh look at cost-efficiency and casts the craft of transport planning in new light, allowing engineers and urban planners to understand the benefits of breaking mobility-centric systems that favour cars and prioritising multi-modal transport systems that promote access. It features in-depth analysis of traditional methods and how these are changing due to new technologies, financial constraints and evolving environmental trends